Effectiveness of a Planned Teaching Program on Maternal Knowledge Regarding the Universal Immunization Program: A Pre-Experimental Study in Mandi District, Himachal Pradesh - Dhanda, Kunal; Sehrawat, Sweta (Journal of Research in Vocational Education, 2026)
Introduction: Immunization is a tool for controlling and eliminating life threatening six infectious and vaccine preventable diseases like tuberculosis, tetanus, diphtheria, whooping cough and polio mellitus and is estimated to avert between 2 and 3 million deaths per year. Since mothers are the important health decision makers of their children, their Knowledge & Practices regarding immunization in general have a great impact on immunization status of their child. The study aims to assess the knowledge level of mothers of under five years children regarding immunization. To find the association between knowledge score regarding universal immunization programme among mothers of under 5 years children and with their selected socio demographic variables. Methodology: Pre experimental research design is used to check effectiveness of planned teaching programme on knowledge regarding universal immunization programme among mothers of under 5 years children. Total 60 mothers were enrolled into the study by using purposive sampling technique. Self - structured knowledge questionnaire was used to assess the knowledge regarding universal immunization programme among the mothers of under 5 years children. Result: The result of the study depicts that that about of 60 mothers, 45 (75%) mothers of under 5 years children had moderate knowledge whereas 15 (25%) mothers of under 5 years children had inadequate knowledge and none of them had adequate knowledge regarding universal immunization programme. The association of knowledge of study participants regarding universal immunization programme was not found to be statistically significant any of the demographical factor’s studies except the educational qualification and source of information. Conclusion: The result from this study revealed that knowledge regarding universal immunization programme among mothers was moderate. Also, the educational programme significantly improved the knowledge of mothers regarding immunization so other teaching strategies can be used increase mothers’ knowledge regarding immunization programme.